पंजी-प्रबन्ध : वंश परिचय प्रथम भाग - (:unkn) unknown (Ankit Prakashan Darbhanga Bihar, 2010)
Panjee-Prabandh is a Geneological Record of Maithil Brahmins collected from various renowned Panjikars. This volume has the record of 19 families.
Panjee-Prabandh : Vansh Parichaya Vol.-I
Keywords: Maithili; पंजी-प्रबन्ध, वंश परिचय; Panjee-Prabandh; Vansh Parichaya; Geneological Record Management; Maithili; Maithili